Reading Comprehension Assessment through Retelling: Performance Profiles of Children with Dyslexia and Language-Based Learning Disability - Kida, Adriana de S. B.; Ávila, Clara R. B. de; Capellini, Simone A. (Frontiers in Psychology, 2016)
Abstract Purpose: To study reading comprehension performance profiles of children with dyslexia as well as language-based learning disability by means of retelling tasks. Method: 105 children from second to fifth grades of elementary school were gathered into six groups: Dyslexia group (D; n=19), Language-based learning disability group (LBLD; n=16); their respective control groups paired according to different variables - age, gender, grade and school system (public or private) (D-control and LBLD-control); and other control groups paired according to different reading accuracy (D-accuracy; LBLD-accuracy). All of the children read an expository text and orally retold the story as they understood it. The analysis quantified propositions (main ideas and details) and retold links. A retelling reference standard (3-0) was also established from the best to the worst performance. We compared both clinical groups (D and LBLD) with their respective control groups by means of Mann-Whitney tests. Results: D showed the same total of propositions, links and reference standards as D-control, but performed better than D-accuracy in macro structural (total of links) and super structural (retelling reference standard) measures. Results suggest that dyslexic children are able to use their linguistic competence and their own background knowledge to minimize the effects of their decoding deficit, especially at the highest text processing levels. LBLD performed worse than LBLD-control in all of the retelling measures and LBLD showed worse performance than LBLD-accuracy in the total retold links and retelling reference standard. Those results suggest that both decoding and linguistic difficulties affect reading comprehension. Moreover, the linguistic deficits presented by LBLD students do not allow these pupils to perform as competently in terms of text comprehension as the children with dyslexia do. Thus, failure in the macro and super-structural information processing of the expository text were evidenced. Conclusion: Each clinical group showed a different retelling profile. Such findings support the view that there are differences between these two clinical populations in the non-phonological dimensions of language.